Trust Based Buyer-Supplier Relationship Will Further Assist Boots.com's Business Development Strategy for Product Line Extension - Lin, Yen-Hui (2008)
In the last twenty years the research on inter-organizational relationship has been growing, it circles around the idea that intensive competition in the marketplace is making it too expensive for one firm to do everything on its own. The widespread belief that companies should focus on their core competencies (Prahalad and Hamel, 1990) has led to an outsourcing trend and in increasing awareness of the importance of a competitive supply base.